2016
DOI: 10.1016/j.molp.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

An INDEHISCENT-Controlled Auxin Response Specifies the Separation Layer in Early Arabidopsis Fruit

Abstract: Seed dispersal is an important moment in the life cycle of a plant species. In Arabidopsis thaliana, it is dependent on transcription factor INDEHISCENT (IND)-mediated specification of a separation layer in the dehiscence zone found in the margin between the valves (carpel walls) and the central replum of the developing fruit. It was proposed that IND specifies the separation layer by inducing a local auxin minimum at late stages of fruit development. Here we show that morphological differences between the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 41 publications
5
33
0
Order By: Relevance
“…A recent study in A . thaliana showed that cell differentiation related to dehiscence zone formation is initiated in open flowers after pollination (van Gelderen et al ., ), which closely corresponds to the developmental stage where first signs of dehiscence zone differentiation were also detected in the dehiscent morph of Ae . arabicum (Figures and S2).…”
Section: Discussionsupporting
confidence: 63%
“…A recent study in A . thaliana showed that cell differentiation related to dehiscence zone formation is initiated in open flowers after pollination (van Gelderen et al ., ), which closely corresponds to the developmental stage where first signs of dehiscence zone differentiation were also detected in the dehiscent morph of Ae . arabicum (Figures and S2).…”
Section: Discussionsupporting
confidence: 63%
“…In this new study (van Gelderen et al, 2016), the authors first confirmed that dehiscence zone formation does take place at the early fruit stages 14-16, as previously reported (Wu et al, 2006). As expected, no cell division or differentiation events occurred in this region in the shatter-resistant ind-2 mutant, also in line with previous findings (Liljegren et al, 2004).…”
Section: Fruit Dehiscence: With or Without Auxin?supporting
confidence: 90%
“…In stage 17B, the authors confirm that also with the DR5 reporter an auxin minimum is present at the separation layer (van Gelderen et al, 2016), as previously reported (Sorefan et al, 2009). In the ind-2 mutant fruits, based on analysis with the DR5 reporter, the auxin response around the valve margins was low from stage 13-17A, and at stage 17B a sudden increase of auxin response in the replum was observed (van Gelderen et al, 2016).…”
Section: Fruit Dehiscence: With or Without Auxin?supporting
confidence: 83%
See 2 more Smart Citations